POLA PERUBAHAN FONOLOGI ANTARA BAHASA MINANGKABAU UMUM DAN SUBDIALEK MINANGKABAU SELAYO - Razin, Thariq; Subiyanto, Agus (Widyaparwa, 2024)
This study aims to formulate the rules that apply to the pattern of phonological changes between the general Minangkabau language and the Selayo Minangkabau language subdialect based on distinguishing features in the study of generative transformation phonology. This research is a comparative descriptive of sound changes in general Minangkabau language and Selayo Minangkabau language subdialect. This research took three stages, namely collection, analysis, and presentation. Collection includes observation and interview. Analysis includes reduction. Presentation includes the use of International Phonetics Alphabeth symbols and narration. The results of the analysis show that there are sound differences that occur between the general Minangkabau language and the Selayo Minangkabau language in the form of vowel changes and deletions. Vowel changes occur in the form of alternation of the vowel /a/ in general Minangkabau then becomes the vowel /e/ in Selayo Minangkabau. This vowel change occurs in two positions, namely the end of the word before the consonants /k/ and /h/ and the end of the word without any consonants or vowels. Sound deletion occurs in the form of the removal of the vowel /i/ in general Minangkabau and then becomes /Ø/ in Selayo Minangkabau. Therefore, Selayo Minangkabau always emphasizes the vowel /u/ at the end of words because the deletion of the vowel /i/ always occurs after the vowel /u/ in Selayo Minangkabau.Penelitian ini bertujuan merumuskan kaidah yang berlaku terhadap pola perubahan fonologi antara bahasa Minangkabau umum dan subdialek bahasa Minangkabau Selayo berdasarkan fitur pembeda dalam kajian fonologi transformasi generatif. Penelitian ini merupakan deskriptif komparatif perubahan bunyibahasa Minangkabau umum dan subdialek bahasa Minangkabau Selayo. Penelitian ini menempuh tiga tahap, yaitu pengumpulan, analisis, dan penyajian. Pengumpulan meliputi observasi dan wawancara. Analisis meliputi reduksi. Penyajian meliputi penggunaan simbol International Phonetics Alphabeth dan narasi. Hasil analisis menunjukkan adanya perbedaan bunyi yang terjadi antara bahasa Minangkabau umum dan bahasa Minangkabau Selayo berupa perubahan vokal dan pelesapan. Perubahan vokal terjadi dalam bentuk pergantian vokal /a/ dalam bahasa Minangkabau umum kemudian menjadi vokal /e/ dalam bahasa Minangkabau Selayo. Perubahan vokal ini terjadi di dua posisi, yaitu akhir kata sebelum konsonan /k/ dan /h/ dan akhir kata tanpa ada konsonan maupun vokal. Pelesapan bunyi terjadi dalam bentuk penghilangan vokal /i/ dalam bahasa Minangkabau umum kemudian menjadi /Ø/ dalam bahasa Minangkabau Selayo. Oleh sebab itu,bahasa Minangkabau Selayo selalu menonjolkan vokal /u/ di akhir kata karena pelesapan vokal /i/ selalu terjadi setelah vokal /u/ dalam bahasa Minangkabau Selayo.This study aims to formulate the rules that apply to the pattern of phonological changes between the general Minangkabau language and the Selayo Minangkabau language subdialect based on distinguishing features in the study of generative transformation phonology. This research is a comparative descriptive of sound changes in general Minangkabau language and Selayo Minangkabau language subdialect. This research took three stages, namely collection, analysis, and presentation. Collection includes observation and interview. Analysis includes reduction. Presentation includes the use of International Phonetics Alphabeth symbols and narration. The results of the analysis show that there are sound differences that occur between the general Minangkabau language and the Selayo Minangkabau language in the form of vowel changes and deletions. Vowel changes occur in the form of alternation of the vowel /a/ in general Minangkabau then becomes the vowel /e/ in Selayo Minangkabau. This vowel change occurs in two positions, namely the end of the word before the consonants /k/ and /h/ and the end of the word without any consonants or vowels. Sound deletion occurs in the form of the removal of the vowel /i/ in general Minangkabau and then becomes /Ø/ in Selayo Minangkabau. Therefore, Selayo Minangkabau always emphasizes the vowel /u/ at the end of words because the deletion of the vowel /i/ always occurs after the vowel /u/ in Selayo Minangkabau.